Multiple Lenses of N-Isotopes Reveal Active Dissolved Organic Nitrogen Cycling in a Subtropical Estuary and Marginal Sea - Zhong, Xiaosong; Yan, Maojun; Xu, Wenqi; Yan, Zhenwei; Xu, Feng; Dong, Shuhang; Xin, Yu; Shi, Xiaoyong (Frontiers in Marine Science, 2022)
Dissolved organic nitrogen (DON) is an important component of the marine nitrogen (N) inventory and plays an essential role in N-cycling in global estuaries and marginal seas. Understanding DON cycling is important but challenging. Global estuaries and marginal seas are experiencing significant anthropogenic impacts and have intensive physical/biochemical gradients, therefore high-quality DON concentration and N-isotope (δ15N-DON) data are very difficult to obtain. To enrich this knowledge, we take the Changjiang Estuary and the adjacent East China Sea shelf seas (CEECS) as a representative example and analyzed multiple isotopes and concentrations of nitrate (NO3-), particulate organic nitrogen (PN), and DON. N isotopes combined with OMP analysis are proved to be very informative. This integrated analysis discriminates active DON production and consumption from a seemingly conservative distribution pattern of DON. The study area was divided into DON production zones 1 and 2 (P-zone 1 and 2) and DON consumption zones 1 and 2 (C-zone 1 and 2). For P-zone 1, the PN-originated DON elevated the δ15N-DON while in P-zone 2, the DON excreted by phytoplankton was characterized by low δ15N and lowered the δ15N-DON. DON consumption occurred in the NO3--depleted surface waters (C-zone 1), as well as the shelf middle and bottom waters (C-zone 2). This study discovers and consolidates the active and dynamical zoning of DON cycling from the estuary to the offshore marginal sea, and establishes a useful means that is of valuable references to DON cycling studying in the global estuaries and marginal seas.